2007
DOI: 10.1519/00124278-200702000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hamstring-Emphasized Resistance Training on Hamstring

Abstract: Holcomb, W.R., M.D. Rubley, H.J. Lee, and M.A.Guadagnoli. Effect of hamstring-emphasized resistance training on hamstring:quadriceps strength ratios. J. Strength Cond. Res. 21(1):41-47. 2007.-A decreased hamstring:quadriceps (H:Q) ratio may put the hamstrings and anterior cruciate ligament (ACL) at increased risk of injury. Therefore, the purpose of this study was to evaluate H:Q ratios of 12 female National Collegiate Athletic Association soccer players, and to test the effects of a 6-week strength training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…The functional H/Q strength ratios in our study are consistent with those reported in previous studies that calculated the functional ratio for knee extension during the entire range [15,22,[28][29][30][31][32][33] . Besides, the functional H/Q strength ratios reported in our study were higher for the end ranges of knee extension (1.0-1.10 for 60°/s and 1.51-1.54 for 180°/s) than during the entire range of knee extension.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The functional H/Q strength ratios in our study are consistent with those reported in previous studies that calculated the functional ratio for knee extension during the entire range [15,22,[28][29][30][31][32][33] . Besides, the functional H/Q strength ratios reported in our study were higher for the end ranges of knee extension (1.0-1.10 for 60°/s and 1.51-1.54 for 180°/s) than during the entire range of knee extension.…”
Section: Discussionsupporting
confidence: 91%
“…If the pre-season hamstring to quadriceps ratio was lower than 0.6 at 180°/s angular velocity the risk of hamstring injury was 17 times higher in competitive sprinters [20] . Studies have reported that injury, detraining or training might have impacts on the changes of normal reciprocal strength distribution around the knee joint [21,22] . Few studies have investigated the impacts of static stretching during the pre-participation training routine on these strength ratios, and those data that are available are conflicting [23,24] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that females with relatively lower H/Q ratios may be at a higher risk for injury (19,20). To prevent knee injuries, an H/Q ratio of 0.6 at a minimum (the hamstrings being 60% as strong as the quadriceps) is accepted (19,21). Evidence suggests that highly developed quadriceps muscles, to a great extent, contribute to the force capacity of hamstring muscles and imbalance of the muscles (19,22).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have examined the ways of improving H/Q ratios (23,24). It was suggested that plyometric exercises improved the ratio in physically active woman and whole body vibration training was effective on moderately active females (21,23,24). However, it is not exactly known whether aerobic exercises or spinal stability training has any impact on knee muscle strength and the H/Q ratio, and which exercise is more effective for the knee muscles in adult women.…”
Section: Introductionmentioning
confidence: 99%
“…Several injury prevention protocols including eccentric exercises such as the Nordic Curl (Gabbe, Branson, & Bennell, 2006;Petersen, Thorborg, Nielsen, Budtz-Jorgensen, & Holmich, 2011), double-leg dead lift (Holcomb, Rubley, Heather, & Guadagnoli, 2007), or leg curl using a fly wheel yo-yo machine (Askling, Karlsson, & Thorstensson, 2003) have shown to successfully attenuate the incidence of hamstring injuries (Opar, Williams, & Shield, 2012). These protective effects have been associated with some specific muscular adaptations such as increased isometric (Kilgallon, Donnelly, & Shafat, 2007) or dynamic (Mjølsnes, Arnason, Østhagen, Raastad, & Bahr, 2004) hamstring strength and a shift of the optimal knee flexion peak torque towards a more open angle position (Brughelli & Cronin, 2007;Clark, Bryant, Culgan, & Hartley, 2005).…”
Section: Introductionmentioning
confidence: 99%